The Impact Of Experiential Marketing Dimensions On Customer Satisfaction And The Emergence Of Word Of Mouth - Farouk, Farouk; Helia, Suhelmi; Eliza, Yulina (AIBPM Publisher, 2024)
This study aims to see the effect of 1) The effect of sense experience on customer satisfaction. 2). The effect of Feel experience on customer satisfaction. 3). the effect of think experience on customer satisfaction. 4). the impact of act insight on consumer loyalty. 5). The effect of relate experience on customer satisfaction. 6). the effect of customer satisfaction on word of mouth. The results of this study indicate that 1). Sense experience fundamentally affects consumer loyalty. 2). Feel experience has a significant effect on customer satisfaction. 3). Think experience fundamentally affects consumer loyalty. 4). Act experience essentially affects consumer loyalty. 5). Relate experience fundamentally affects consumer loyalty. 6). Consumer loyalty fundamentally affects verbal. Variable sense insight, Feel insight, think insight, act insight, relate insight with a critical worth of 0.00<0.05 and variable Consumer loyalty with a huge worth of 0.00 <0.05. The author suggests that promotional activities through word of mouth can continue to be improved in the future because this will be able to increase consumer trust and loyalty and improve experiental marketing by paying attention to sense insight, Feel insight, think insight, act insight, relate insight.